The incredible journey of the butterflies [videorecording (DVD)] - De Pencier, Nick; Channing, Stockard (PBS Video, 2009)
Every year monarch butterflies migrate across North America to a remote area of Mexico. This presentation discusses how the butterflies navigate and endure the long journey and takes you to the locations they call home.